Polymorphisms in Oxytocin and alpha(1a) Adrenergic Receptor Genes and Their Effects on Production Traits in Dairy Buffaloes - Araujo, Daniele Neves [UNESP]; Camargo, Gregorio Miguel Ferreira de [UNESP]; Fonseca, Patricia Dias da Silva [UNESP]; Cardoso, Diercles Francisco [UNESP]; Hurtado-Lugo, Naudin Alejandro [UNESP]; Aspilcueta-Borquis, Rusbel Raul [UNESP]; Tonhati, Humberto [UNESP] (Taylor &francis Inc, 2015)
The use of molecular markers may auxiliary the buffalo breeding. The oxytocin (OXT) and the adrenergic receptor alpha(1A) (ADRA1A) may be involved in milk ejection in ruminants. The aim of this study was to verify the existence of polymorphisms in the OXT and ADRA1A genes and their associations with milk production traits. A total of 220 buffaloes were genotyped using PCR-RFLP for both genes. The SNP identified in the ADRA1A gene was associated with protein percentage in dairy buffaloes. This is the first report of such association in the literature, which has not been studied in other species.
Keywords: Milk ejection; SNP; Bubalis bubalis; Molecular markers